A Truthful Generalization of Black‐Scholes‐Merton. Issue 111 (1st February 2021) - Ayache, Elie
Abstract : BSM was never equipped to face an options market. The formula doesn't know what an options market is and even less so what the meaning of inverting the formula and implying volatility from the option market price could possibly be.